Appraisal of effectiveness and comparison of parent-child interaction therapy and parent management training on symptom improvement of ADHD among boys with ADHD - Farzaneh Michaeli Manee; Nargess Nourizad; Sepideh Behnejad; Rasha Haggi (Gonabad University of Medical Sciences, 2018)
Parenting a child who has ADHD presents most parents with many challenges. The aim of study was to appraise the effectiveness and comparison of parent-child interaction therapy (PCIT) and parent management training (PMT) to mothers in symptom improvement of 8-10 year old boys with ADHD in Urmia. A quasi-experimental pretest-posttest design with a control group was used. The population consisted of all mothers of 8-10 year old boys with ADHD in Urmia in 2012 who were referred to the counseling and treatment centers and their children received ADHD combined type diagnosis. Children who had the highest scores in Conner's Rating Scale (teachers & parents) were considered as ADHD patients that 45 patients were selected by convenience sampling method and were assigned randomly into two experimental groups (n=15)and a control group. Then, experimental groups were trained by Eyberg's PCIT and Patterson's PMT during 9 sessions which were held once a week. The control group received no intervention. In order to collect the study's data Conners Scales and the SWAN Rating Scale for ADHD were used. Data analysis was done by analysis of covariance with SPSS-16 software. The results showed that the difference between pretest and posttest scores of control group is equal to F=185.23 that it is significant (p<0.01). Results of Tukey's test showed that there was significant difference between the PCIT and PMT at level of 0.05 and this effect was stronger for PCIT group. Overall, it can be concluded that both of the programs were effective in relieving the ADHD symptoms but the PCIT was more effective.